Can neurodegeneration be separated from neuropathological hallmarks of chronic idiopathic human neurodegenerative disease? A perspective from modelling!. (20th July 2011) - Paine, Simon; Lowe, James; Bedford, Lynn; Mayer, R. John
Abstract : Chronic neurodegenerative disease is characterized by extensive regional loss of neurons in the brain and neuropathological hallmarks in surviving neurones. Genetic modelling by overexpression of hallmark proteins does not produce extensive neurodegeneration, whereas genetic deletion of neuronal 26S proteasomes does, as well as some hallmarks of human disease.